Simplification and cost reduction of visual corona tests. Issue 4 (12th January 2018) - Riba, Jordi‐Roger; Abomailek, Carlos; Casals‐Torrens, Pau; Capelli, Francesca
Abstract : Visual corona tests are useful to identify the critical corona points of different high‐voltage components. Radio interference voltage and partial discharge measurements also allow detecting corona activity. However, these techniques require expensive screened laboratories, sophisticated instrumentation and usually do not provide the exact location of the discharges. Corona tests are often performed in external laboratories, where customers habitually have to face long waiting times. The tests in such laboratories must be totally planned beforehand, as they are habitually done by external engineers, so little information about the behaviour and possible modifications of the product is acquired by the customer. This study proposes a feasible solution to perform routine corona tests, while greatly reducing the voltage applied, laboratory size and requirements, testing times, and thus test costs. This study also detects the visual corona onset by means of a commercial digital camera, which allows locating the critical corona points, thus greatly decreasing the costs of the corona instrumentation, while maintaining the accuracy and sensitivity of the detection method. The methodology proposed in this study can be applied to many other high‐voltage devices such as conductors, vibration dumpers, corona protections and different types of hardware and fittings for power lines and substations.